The therapeutical approaches for rare diseases through the immune processes of IgG Fc Receptors - Zhan He Wu (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2020)
Fc Receptor for Immunoglobulin G (IgG) is the major class among the five classes of Fc receptors including Fc Receptor for IgA, IgE, IgM and IgD. Three types (type I, II and III) of the Fc Receptors for Immunoglobulin G (FcRγs) on a variety of hematopoietic cells with different structures and different functions were defined by World Health Organisation (WHO).  FcRγs are a group of integral membrane glycoproteins molecules mainly on the surface of effector cells playing very important roles in host defence and regulation in both of the adaptive and innate immune system through signal transduction and other several biological processes after triggered by the immune reactions.  Rare diseases are a group of diseases/disorders occurring in a small percentage of the population commonly with the chronic phase and most of them are genetic based. Data suggested that some types of Rare diseases/disorders such as auto-immune and immune-deficiency are associated diseases associated with dysfunction of Fcγs, even some types of cancer.  Recently, intensive studies on Fcγs from the level of genetics increased the understanding in pathophysiological mechanism of some diseases. Such advances obtained provide the opportunities for the therapeutical approaches for Rare diseases in some types involved in dysregulations of Fcγs.  The aim of this review is to discuss the characterisation of Fcγs from genotype to phenotype and the Fcγs associated Rare diseases including cancers from laboratory bench to clinical bedside.